HMNS, Paris Fashion Week, and the Corruption of Communication - Myrza Fikry Octaviana; Anisa Permata Putri; Chatya Iqlima Huaida; Muhammad Dicky Arfani; Savira Nurindra Putri; Mia Setiawati (Jobmark: Journal of Branding and Marketing Communication, 2021)
At the end of 2021, HMNS Parfume attracted controversy because it made a statement to the public regarding its brand's participation in Paris Fashion Week 2022. Regarding this statement, HMNS was indicated to have manipulated messages conveyed via its official Instagram social media and the Twitter account (now: X) of the owner of HMNS. This article aims to analyze the method of communication carried out by HMNS Perfume through the theory of Communication Corruption. Communication corruption is an action or event in a communication process that reduces the right of the communicant or audience to receive the message entirely and correctly according to the facts, both normative and contemplative. Communication corruption has four dimensions: message, media, context, and behavior. The results of the analysis show that HMNS Perfume carried out communication corruption in the message dimension through confessions in Instagram captions and explanations from the HMNS owner, the media dimension through misuse of social media on Instagram and Twitter, the context dimension through confessions that did not occur to increase exclusivity, sound perception, and public reputation, and from the behavioral dimension through deceptive or misleading communication strategies to enhance their image or attract consumer interest. The results of this analysis can provide lessons for brands to pay attention to aspects of communication corruption to avoid damaging brand reputation.